In situ construction strategy for three-dimensional Janus cellulose aerogel with highly efficient oil–water separation performance: from hydrophobicity to asymmetric wettability. Issue 18 (31st August 2022) - Fei, Yongsheng; Tan, Yujin; Deng, Yuyi; Xia, Pengzhe; Cheng, Jingru; Wang, Congcong; Zhang, Jingjing; Niu, Chenxi; Fu, Qian; Lu, Lingbin
Abstract : At present, oil pollution on water has caused a disastrous and inestimable impact on the ecological environment and economic development. There is an urgent need for highly efficient materials for oil–water separation. Abstract : At present, oil pollution on water has caused a disastrous and inestimable impact on the ecological environment and economic development. There is an urgent need for highly efficient materials for oil–water separation. There has been extensive research on Janus structural materials for use as novel oil–water separation materials. Herein, we developed an in situ construction strategy for the three-dimensional (3D) Janus structure based on a hydrophobic matrix and used a facile method to construct a 3D Janus structural cellulose aerogel with asymmetric wettability. Vacuum-assisted chemical vapor deposition technology was used to modify cellulose aerogel for the hydrophobic matrix. The hydrophilic layer was formed by coating dopamine with in situ polymerization on one side of the hydrophobic matrix. Moreover, the oxidative polymerization of dopamine in organic solution was investigated. The 3D Janus structural cellulose aerogel showed opposite wettability, with hydrophobicity on one side with a water contact angle of 142° and hydrophilicity on the other side. Due to the asymmetric wettability and interconnected network structure, the material achieved highly efficient separation performance for various mixtures of oil and water, even water-in-oil emulsion, with a penetration flux up to 3121 L m −2 h −1 and separation efficiency of 99.5%, driven only by gravity. The droplet size in the recycled filtrate was measured as 0.5–2 nm. In this work, we not only developed a novel, highly efficient, and environmentally friendly oil–water separation material for the field of water treatment, but we also provide a new construction strategy and a scientifically significant reference for Janus structural porous materials.